Extensive genome analysis identifies novel plasmid families in Clostridium perfringens. Issue 4 (20th April 2023) - Gulliver, Emily L.; Adams, Vicki; Marcelino, Vanessa Rossetto; Gould, Jodee; Rutten, Emily L.; Powell, David R.; Young, Remy B.; D'Adamo, Gemma L.; Hemphill, Jamia; Solari, Sean M.; Revitt-Mills, Sarah A.; Munn, Samantha; et al.
Abstract : Globally, the anaerobic bacterium Clostridium perfringens causes severe disease in a wide array of hosts; however, C. perfringens strains are also carried asymptomatically. Accessory genes are responsible for much of the observed phenotypic variation and virulence within this species, with toxins frequently encoded on conjugative plasmids and many isolates carrying up to 10 plasmids. Despite this unusual biology, current genomic analyses have largely excluded isolates from healthy hosts or environmental sources. Accessory genomes, including plasmids, also have often been excluded from broader scale phylogenetic investigations. Here we interrogate a comprehensive collection of 464 C . perfringens genomes and identify the first putative non-conjugative enterotoxin (CPE)-encoding plasmids and a putative novel conjugative locus (Bcp) with sequence similarity to a locus reported from Clostridium botulinum . We sequenced and archived 102 new C. perfringens genomes, including those from rarely sequenced toxinotype B, C, D and E isolates. Long-read sequencing of 11 C . perfringens strains representing all toxinotypes (A–G) identified 55 plasmids from nine distinct plasmid groups. Interrogation of the 464 genomes in this collection identified 1045 plasmid-like contigs from the nine plasmid families, with a wide distribution across the C. perfringens isolates. Plasmids and plasmid diversity play an essential role in C. perfringens pathogenicity and broader biology. We have expanded the C. perfringens genome collection to include temporal, spatial and phenotypically diverse isolates including those carried asymptomatically in the gastrointestinal microbiome. This analysis has resulted in the identification of novel C. perfringens plasmids whilst providing a comprehensive understanding of species diversity.